Performance of zirconia ceramic cantilever fixed dental prostheses: 3-year results from a prospective, randomized, controlled pilot study - Zenthöfer, Andreas; Ohlmann, Brigitte; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2015)
STATEMENT OF PROBLEM: Little is known about the clinical performance of ceramic cantilever fixed dental prostheses on natural teeth. - PURPOSE: The purpose of this randomized controlled pilot study was to evaluate the clinical performance of ceramic and metal ceramic cantilever fixed dental prostheses (CFDPs) after 3 years of service. - MATERIAL AND METHODS: Twenty-one participants were randomly allocated to 2 treatment groups. Participants in the ceramic (ZC) group (n=11) each received 1 CFDP made of yttria-stabilized, tetragonal zirconia polycrystal; the others (n=10) were fitted with a metal ceramic (MC) CFDP. All CFDPs were retained by 2 complete crown abutments and replaced 1 tooth. The clinical target variables were survival, incidence of complications, probing pocket depth (PPD), probing attachment level (PAL), plaque index (PI), gingival index (GI), and esthetic performance as rated by the participants. The United States Public Health Service (USPHS) criteria were used to evaluate chipping, retention, color, marginal integrity, and secondary caries. Descriptive statistics and nonparametric analyses were applied to the target variables in the 2 groups. The esthetic performance of the CFDPs was also visualized by using a pyramid comparison. - RESULTS: The overall survival of the CFDPs was 100% in both groups. During the 3-year study, 6 clinically relevant complications requiring aftercare were observed among 5 participants (4 in the ZC group and 2 in the MC group). Changes in the PI, GI, PPD, and PAL of the abutment teeth were similar for both groups (P>.05). The participants regarded the esthetic performance of ZC-CFDPs and MC-CFDPs as satisfactory. - CONCLUSIONS: Within the 3-year observation period, the clinical performance of MC-FDPs and ZC-FDPs was acceptable. More extensive research with larger sample sizes is encouraged, however, to confirm the evaluation of the survival of Y-TZP hand-veneered cantilever FPDs.